2019
DOI: 10.1519/jsc.0000000000003352
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Collegiate Athlete Blood Biomarkers at Moderate Altitude

Abstract: Morris, KL, Widstrom, L, Goodrich, J, Poddar, S, Rueda, M, Holliday, M, San Millian, I, and Byrnes, WC. A retrospective analysis of collegiate athlete blood biomarkers at moderate altitude. J Strength Cond Res 33(11): 2913–2919, 2019—Blood biomarkers are used to assess overall health and determine positive/negative adaptations to training/environmental stimuli. This study aimed to describe the changes in blood biomarkers in collegiate football (FB) (n = 31) and cross-country (XC) (n = 29; 16 women [FXC], 13 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Although we found no anemia in the Kendo practitioners studied, a previous report on elite young athletes found a low incidence (~7%) of anemia in both males and females [21]. The iron status, however, exhibited a significant difference between genders -i.e., a significant higher proportion of iron deficiency was observed in female athletes in our study, which is consistent with previous reports [21,22]. The causes of gender differences in iron deficiency include menstrual blood loss and, consequently, inadequate iron intake in females [23,24].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although we found no anemia in the Kendo practitioners studied, a previous report on elite young athletes found a low incidence (~7%) of anemia in both males and females [21]. The iron status, however, exhibited a significant difference between genders -i.e., a significant higher proportion of iron deficiency was observed in female athletes in our study, which is consistent with previous reports [21,22]. The causes of gender differences in iron deficiency include menstrual blood loss and, consequently, inadequate iron intake in females [23,24].…”
Section: Discussionsupporting
confidence: 93%
“…We performed a sub-analysis to figure out the characteristics of female practitioners with hypoferritinemia [20,22] 20 [20,22] 20 [19,21] Years of sports/athletics 15 [13,17] 15 [13,17] 15 [13,17] Body mass index (kg/m 2 ) 24. (serum ferritin levels ≤30 ng/mL) when compared to those with > 30 ng/mL of serum ferritin (Table 2).…”
Section: Comparison Of Characteristics Between Hypo-and Normoferritinmentioning
confidence: 99%
“…Total CK activity is a widely used measurement in monitoring of the training load, physical efficacy and overtraining [ 17 , 33 ]. Morris et al [ 34 ] demonstrated that muscle damage biomarkers increased over time and exceeded the normal reference ranges at moderate altitude (hyperbaric hypoxia), indicating cell damage pathology. Hypoxia impairs injured muscles rebuilding in patients with chronic obstructive pulmonary disease and peripheral arterial disease, but it has a positive effect on the muscle regenerative capacity in athletes [ 7 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these parameters are often complex to analyze as they are strongly dependent on factors such as age, gender, health and nutritional status and diseases (Morris et al, 2019). The first erythropoietic response to altitude is dependent on both hypoxic dose and iron stores (Serpell et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly speaking, the greatest effects of hypoxia on the haematological parameters occur at 2200–2500 m, with a minimum exposure of 12 h/day for a minimum period of 3 weeks (Millet, Roels, Schmitt, Woorons, & Richalet, 2010). Research studies have specifically highlighted the role of sFER in maintaining blood cell homeostasis and turnover during living or training at altitude (Latunde‐Dada, Vulpe, Anderson, Simpson, & McKie, 2004; Mairbäurl, Ruppe, & Bärtsch, 2013; Morris et al, 2019). Ferritin is a globular protein which serves to store iron in a non‐toxic form in the cells and to transport it where is required, particularly it can store up to 4500 atoms of iron.…”
Section: Introductionmentioning
confidence: 99%